MODELLING THERMAL SHOCK BASED CRACKING BEHAVIOUR OF ARMOUR MATERIAL FOR FUSION REACTOR - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Abstract -This study presents a computational model for studying the mechanical effects of thermal shock over armour material used for fusion reactor. The simulation study comprises of transient thermal shocks over the bulk substance for a period of 1ms. Latter on the cracking behaviour is predicted by extending the virtual crack growth for screening out the efficacy of the used material and its composition. Â